The merit principle in the public personnel regime in Türkiye: recent trends through the decisions of the Council of State - Abdurrahman Muhammet Banazılı; Umut Turgut Yıldırım (Hitit Sosyal Bilimler Dergisi, 2026)
This study analyzes the judicial interpretation of merit principle in public administration within the framework of the current Council of State decisions. The main problem of the research concerns the normative criteria the administrative judiciary uses to assess the principle of merit, and its resultant consequences for the interrelation between administration’s discretion and rule of law. A deficiency in Turkish discourse on merit tends to discuss it exclusively within the purview of constitutional norms, legislation and theory, while studies thematically focusing on the case law of the Council of State are scarce. The analysis was designed in accordance with a qualitative legal research design, and Council of State decisions were examined by document analysis. As many as 190 decisions related to the public personnel regime and merit were reviewed. To ensure the representation of thematic diversity, the cases were selected using a purposive sampling technique. In this context forty-nine decisions were analyzed, divided into four thematic classes: Dismissal procedures, promotion and career processes, security investigations and disciplinary procedures, examination and objective evaluation, and regulatory procedures. The sample size was determined by data saturation and thematic representation. A research design emerged that reveals trends in case law at an analytical level. The results are, in fact, that there is an interpretation framework for the merit principle in Council of State’s case law which is adapted according to dispute types. Dismissal and career decisions reveal that there should be concrete motives for administrative acts. In security investigations and disciplinary matters, the procedural guarantee dimension of the merit principle is highlighted. In decisions concerning examination and evaluation mechanisms there is special emphasis on the presence of objective criteria; in case law concerning regulatory acts it is pointed out that the normative discretion granted to administration should not be exercised in a way that conflicts with merit. The principle of merit is discussed in Council of State decisions within a multilayered judicial approach that both protects the effectiveness of administration and supervises administrative procedures in the principles of legal certainty and proportionality, respectively. Within that field, the research develops an analytical framework for assessing merit discussions within the case law literature.